Prospołeczna orientacja firm produkujących żywność - Rak, Lech (Social Orientation of Food Producers, 2006)
The article shows the problems of social oriented marketing. "Green marketing" is an example of company activities in sustainable development circumstances. The article presents the possibility of the practical application of marketing tools in the companies which produce animal food.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 48-59